Simple and Efficient Epinephrine Sensor Based on Palladium Doped Poly(L-arginine) Modified Electrode - Li, Hui; Sun, Dengming (Asian Journal of Chemistry, 2015)
A novel palladium doped poly(L-arginine) modified electrode (Pd-PLA/GCE), fabricated by electrochemical immobilization of the palladium doped poly(L-arginine) on a glassy carbon electrode, was used for determination of epinephrine through cyclic voltammetry. The electrochemical properties of epinephrine have been investigated. In phosphate buffer solution (pH 3.0), a pair of redox peaks was observed with potential Epa = 0.500 V and Epc = 0.406 V at a scan rate of 160 mV/s. Epinephrine was determined at the modified electrode under the optimum conditions by both cyclic voltammetry and differential pulse voltammetry. The results show that the peak current and the concentration of epinephrine show good linear relation in a range of 5.00 × 10-7 1.00 × 10-5 mol/L and 1.00 × 10-5 1.00 × 10-4 mol/L with detection limit of 1.0 × 10-7 and 8.0 × 10-8 mol/L. The method was successfully applied to the determination of epinephrine in injection with satisfactory results.